Oral health awareness and practices of primary school teachers in ibadan, Nigeria (2014)
he school is an important avenue for promoting oral health most especially in developing countries with low resources. However, the success of any school based preventive oral health programme is dependent on the teachers about whom there is little information on their present state of oral health awareness and practices in Ibadan, South-western Nigeria. To investigate the oral health awareness and practices of primary school teachers in Ibadan, Nigeria. A cross sectional study of randomly selected public primary school teachers in Ibadan was performed. Data were collected using structured self-administered questionnaire, which assessed their socio-demographic characteristics, oral health awareness, oral hygiene measures and utilization of dental services. Data were analyzed using SPSS version 21. Chi square statistics was used to test for association between variables and p value set at < 0.05. Results: A representative sample of 309 teachers participated in the study with a mean age of 48.7 (± 5.94) years. The majority, 284 (91.9%), were females. A few, 39 (12.6%), of the teachers knew what dental caries and its causes were, while 1 (0.3%) knew the cause of oral cancer. Only 149 (48.2%) knew that oral diseases could be prevented. If the teachers had problems with their teeth; 154 (49.8%) would go to the hospital, 115 (37.2%) would self-medicate, 20 (6.5%) would visit the drug shop (chemist), 1 (0.3%) would visit the traditional healer and 19 (6.2%) were not sure of what to do. About a third of participants, 99 (32.0%) have had previous consultations with the dentist, with many 72 (72.0%) doing so because of pain. Many of the teachers 183 (59.2%) cleaned their teeth twice or more daily before eating. Male teachers (84.0%) and those with less teaching experience (60.6%) were found spending longer time in cleaning their teeth (p = 0.035 and p = 0.002). Poor oral health awareness and practices still exists among the teachers. There is a need for urgent intervention to promote oral health amongst them